Cassegrian Telescope Design Based on Root-Finding Optimization - Yaseen, Nour Mohammd Hasan; Ahmad, Ahmad K; Khorsheed, Suha M (Al-Nahrain Journal of Science, 2018)
A two-mirror Cassegrian telescope design is presented. The primary mirror is paraboloid with an aperture of 1m in diameter. The secondary mirror is hyperboloid with an aperture that makes a light obstruction of merely 0.25%. The telescope resolving power is twofold the one a spherical primary mirror produces with the same aperture. Aberration elimination is obtained by modifying the radius of curvature of the secondary mirror and also its asphericity factor. Achieving this work demanded constructing a programming code for tracing light rays. This code not only used to tracing the general type of light rays (skew ray) through all Cartesian surfaces but it is also used to exhibit the telescope performance when varying the secondary mirror radius of curvature and its asphericity factor.